Prevalence of dog-mediated rabies in Ethiopia: a systematic review and Meta-analysis from 2010 to 2020 - Shiret Belete; Melke Meseret; Haileyesus Dejene; Ayalew Assefa (BMC, 2021)
Abstract Background Ethiopia accommodates the second largest number of human rabies deaths in Africa. This systematic review and meta-analysis aimed to summarize and pool estimates of dog-mediated rabies status in Ethiopia. Methods Published researches between 2010 and 2020 were comprehensively searched and the required information was extracted. The prevalence was estimated using the random-effects meta-analysis because higher heterogeneity between studies was expected. Results The pooled estimate of rabies was 32% (95% CI: 19-46%), with individual study prevalence estimates ranged from 1 to 78%. Studies were approximately weighted equally with individual weight ranging from 5.19-5.28%. Subgroup analysis indicated that the random pooled prevalence of rabies was 28% (95% CI: 0-81%) in animals and 33% (95% CI: 20-47%) in humans. Furthermore, a subgroup analysis across regions indicated that the pooled prevalence was 78% in Addis Ababa, 46% in Oromia, 40% in Tigray and 5% in Amhara regional states. No single study was reported from the country's eastern and southern parts to be included in this meta-analysis. Conclusion The estimated pooled rabies prevalence was found high and showed varying among study regions. Therefore, focusing on mass dog vaccination campaigns and public awareness should be implemented to control the disease.